Modelling of Disturbing Efects within Communication Channel for Safety-Related Communication System - Maria Franekova; Karol Rastocny (Advances in Electrical and Electronic Engineering, 2007)
The aim of the paper is using of modelling within development of safety–related communication systems presented in the areas where guaranty of safety integrity level is required. In the paper basic principles used in the process of safety evaluation in closed transmission systems are summarised. Dangerous states of system are mainly caused by random failures of HW within non-trusted transmission system, by electromagnetic interference caused with noise or interferences and by systematic failures within specification of system. Main part of paper describes the simulation of disturbing effects within communication channel via programme Matlab, relations for determination of probability of undetected errors of code words with using block codes and results of residual error rate for Hamming code.